2017
DOI: 10.1108/bjm-02-2016-0052
|View full text |Cite
|
Sign up to set email alerts
|

Ethical behaviour and honesty in post-Soviet business environment

Abstract: Purpose The purpose of this paper is to analyse generational differences with regard to honest behaviour and honesty as a personal value in post-Soviet business environment: in Estonia and Latvia. Design/methodology/approach In total, 781 service employees from six retail organizations in Estonia and Latvia were surveyed to assess likelihood of dishonest behaviour and to rank their values according to the Rokeach instrumental value scale. Findings Older generations report higher likelihood of honest behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The result that ethical values affect the perception of others’ behaviour emphasises the socially constructed nature of ethicality: the (dis)belief in others’ ethicality affects our value system to be more aligned with others (Houser et al , 2012; Gächter and Schulz, 2016) and at the same time, we see others similar to our own moral standards (Di Tella et al , 2015). The practical implication of this result would be that hiring honest people seems to be the best safeguard against dishonest behaviour, as admitted by salespeople in Beck and Willis’ (1993) study and concluded by Baumane-Vitolina et al (2017). Therefore, honesty tests that measure a job applicant’s tolerance of deviant behaviour are also of practical relevance (Hollinger and Davis, 2006).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The result that ethical values affect the perception of others’ behaviour emphasises the socially constructed nature of ethicality: the (dis)belief in others’ ethicality affects our value system to be more aligned with others (Houser et al , 2012; Gächter and Schulz, 2016) and at the same time, we see others similar to our own moral standards (Di Tella et al , 2015). The practical implication of this result would be that hiring honest people seems to be the best safeguard against dishonest behaviour, as admitted by salespeople in Beck and Willis’ (1993) study and concluded by Baumane-Vitolina et al (2017). Therefore, honesty tests that measure a job applicant’s tolerance of deviant behaviour are also of practical relevance (Hollinger and Davis, 2006).…”
Section: Discussionmentioning
confidence: 91%
“…Recent research confirms that organisational life varies significantly between Western, Central, and Eastern European countries (Sakowski et al , 2015; Meyer and Peng, 2016; Zupan et al , 2017), but few studies on dishonesty have been conducted outside developed Western societies (e.g. Baumane-Vitolina et al , 2017, which analyses generational differences with regard to ethicality). Post-communist legacy may add an additional layer: documents illustrate that petty illegalities, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Modern HRM is a wicked problem, because trying to change a single agent calls for large system initiatives (Waddock et al 2015). Current HRM faces numerous challenges, such as motivating and keeping elderly employees (Kurek and Rachwał 2011, Sturz and Zografos 2014, Vasconcelos 20152018), while making organizations attractive for Generations Y and Z , Brown et al 2012, Baumane-Vītoliņa et al 2017, Chawla et al 2017, supporting female (Bark et al 2014) and LGBTIQ+ journeys (Köllen 2016, Pichler et al 2017, maintaining an appropriate work environment for people with disabilities (Hogan et al 2012, Kulkarni andRodrigues 2014) and addressing employees' struggles with various lifestyle and health issues, such as diabetes (Stynen et al 2015), obesity (Levay 2014), alcohol and substance abuse (Belhassen and Shani 2012) or helping those suffering from violence at home or at the workplace (Alsaker et al 2016).…”
Section: Cultural Diversity and Human Resource Managementmentioning
confidence: 99%